Experimental study on compressive behavior of GFRP stiffened panels using digital image correlation. (1st March 2016) - Kolanu, Naresh Reddy; Suriya Prakash, S.; Ramji, M.
Abstract: Stiffened composite panels are primary structural components in ship, aircraft and aerospace vehicles. The main objective of this study is to investigate the behavior of glass fiber reinforced polymer (GFRP) composite panels with stiffener runout condition and different stiffener configurations such as blade, T and hat under axial compression. A special fixture was designed and fabricated for the compressive testing of GFRP composite stiffened panels. Fabricated specimens were tested until failure and the effect of different stiffener configurations on the load–deformation behavior is compared. Digital image correlation (DIC) was used to measure the deformations and strains on the GFRP composite panels. Test results indicated that T-stiffeners performed well with higher failure load and stiffness as compared to other stiffeners. DIC results show that the presence of stiffeners reduced the out-of-plane displacement in the stiffened panels. As the load level increases, damage initiates and propagates. The surface strain and displacement are sensitive to damages and it can alter their distribution. This could be captured using DIC technique as the damage distribution takes place. The T-stiffeners were found to be effective in resisting bending strains and produced more uniform distribution of compressive strain compared to other stiffener configuration. Highlights: Compression behavior of GFRP panels with blade, T and hat stiffeners is studied. Digital image correlation (DIC) was used for full-field strain measurement. T-stiffeners were more efficient in strength and stiffness improvement. DIC results show that the stiffeners reduced the out-of-plane displacement.